POLA KOMUNIKASI KELOMPOK FATAYAT NU TANGERANG DALAM PEMBENTUKAN KARAKTER HIDUP SEHAT PADA KEGIATAN “SHARING SEHAT BERSAMA FATAYAT” - Amalliah, Amalliah; Siahaan, Flora Meliana; Yunita, Ria (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
The family is the foundation of the formation of a healthy living character, because it is from the family that the formation of a healthy living character actually begins. Good or bad a person’s healthy way of life is clearly determined by the parenting pattern developed in the family. A mother becomes a good uswatun hasanah for her children, in realizing the child into a whole person who brings goodness to himself, his family, society, country, and the universe (maslahah). Approach The group communication pattern applied is an approach that can be better understood as a pattern of interaction than as a set of specific skills. This study aims to determine the pattern of communication in Healthy Sharing activities with Fatayat. This study was dissected based on the concept of group communication patterns, using a qualitative approach research method with a descriptive method. The results of the research are communication patterns, communication patterns, network communication schemes, all channels or star patterns and communication patterns, group interaction analysis, and character education by interacting and sharing education.